Application of Phytohormones of Bean Sprouts Extract on Growth of Cayenne Pepper (Capsicum frutescens L.) - A Miftakurrohmat; Mohammad Dyland Dewantara (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the phytohormone concentration of bean sprout extract which is effective against the growth of cayenne pepper plants. This research was conducted in the hamlet of Mojosantren, Kelurahan Kemasan, Krian District, Sidoarjo at an altitude of ± 10 m above sea level. The study was conducted in January to March 2020. This study was compiled using a Randomized Block Design (RBD) with 6 treatments and 4 replications to obtain 18 experimental units. Variables observed were the emergence of shoots, plant height, number of leaves, stem diameter, number of branches, flower appearance, root length, and root volume. Data were analyzed with ANOVA variety followed by BNJ with the level of confidence according to the results of the annova. The results showed that there was a very significant influence on the observed variables when the emergence of shoots, plant height, number of leaves, stem diameter, number of branches, root length and root volume. Then the real effect occurs on the observation variable when the flower emerges.